A Study on Microgel System as a Template for Dispersion and Separation of Chiral Tartaric Acid - Mat Lazim, Azwan; Hasbullah, Aishah; M. Yusoff, Siti Fairus; Andarini, Mellissa (Journal of Science and Technology, 2012)
Separation of tartaric acid enantiomers in organic compounds using conventional techniques requires high energy demand, high chemicals consumption, lengthy, complicated and expensive processes. This research demonstrates utilization of PNIPAM microgel system as a template for incorporation of chiral D- and L- tartaric acids (TA). The poly(n-isopropylacrylamide) (PNIPAM) microgel was synthesized using surfactant free emulsion polymerization (SFEP) and was characterized using standard procedures. The combination of 1.4×10-3 g/ml microgel with 3.02×10-4 g/ml TA gave the most stable system. Subsequently, a two-phase system was obtained after centrifugation. Both phases were subjected to dynamic light scattering (DLS) analysis and the corresponding separated systems gave particle sizes ranging from 80-90 nm for the upper phase, and 1200-1500 nm for the lower phase. Scanning electron micrographs showed the presence of agglomeration in the lower phase, supporting the DLS results. Nuclear magnetic resonance (1H NMR) analysis confirmed the presence of TA indicated by a peak at δ = 13.1 ppm. Based on these findings, the system can be a potential alternative template for TA racemix acid dispersion and separation.